Androgen deprivation-induced ZBTB46-PTGS1 signaling promotes neuroendocrine differentiation of prostate cancer. (January 2019) - Chen, Wei-Yu; Zeng, Tao; Wen, Yu-Chng; Yeh, Hsiu-Lien; Jiang, Kuo-Ching; Chen, Wei-Hao; Zhang, Qingfu; Huang, Jiaoti; Liu, Yen-Nien
Abstract: Androgen receptor (AR) targeting is an important therapeutic strategy for treating prostate cancer. Most tumors progress to castration-resistant prostate cancer (CRPC) and develop the neuroendocrine (NE) phenotype under androgen deprivation therapy (ADT). The molecular basis for NE transdifferentiation after ADT remains incompletely understood. Herein, we show that an immunocyte expression protein, ZBTB46, induces inflammatory response gene expression and contributes to NE differentiation of prostate cancer cells. We demonstrated a molecular mechanism whereby ZBTB46 can be regulated by the androgen-responsive gene, SPDEF, and is associated with NE prostate cancer (NEPC) differentiation. In addition, ZBTB46 acts as a transcriptional coactivator that binds to the promoter of prostaglandin-endoperoxide synthase 1 (PTGS1) and transcriptionally regulated PTGS1 levels. Overexpression of ZBTB46 decreases the sensitivity of the combination of enzalutamide and a PTGS1 inhibitor; however, knockdown of ZBTB46 sensitizes the PTGS1 inhibitor and reduces tumor malignancy. ZBTB46 is inversely correlated with SPDEF and is increased in higher tumor grades and small-cell NE prostate cancer (SCNC) patients, which are positively associated with PTGS1. Our findings suggest that the induction of ZBTB46 results in increased PTGS1 expression, which is associated with NEPC progression and linked to the dysregulation of the AR-SPDEF pathway. Highlights: Antagonized AR-SPDEF signaling-induced ZBTB46 exhibits NEPC differentiation. ZBTB46 counteracts the tumor suppressor effects of SPDEF. ZBTB46 positively regulates PTGS1 following ADT. Inhibition of ZBTB46 sensitizes the PTGS1 inhibitor and reduces tumor malignancy. ADT in prostate cancer patients increases ZBTB46-PTGS1 and decreases SPDEF.